Realitas Preferensi Mahasiswa Memutuskan Belajar pada Program Studi Pendidikan Agama Islam - Harahap, Musaddad; Yunita, Yenni; Simbolon, Berby Rumiati (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2025)
The religious education study program is an education program that has a fairly stable chance of accepting new students. The development of the number of students in the Islamic education study program is relatively fluctuating.  Year after year, the number of students is relatively constant. If there is a decrease in the interest of prospective new students, then the decline is not too drastic. Likewise, when there is an increase in interest, the increase is not too significant. The research method chosen in this study is descriptive quantitative, which is to visualize the phenomenon with representative numbers. Data were collected using survey instruments and data analysis using the percentage formula, then presented with a pie chart. The results showed that the main factors influencing student decisions include intention (self-motivation), family encouragement, religious motivation, career prospects, social environment, and ukhrawi paradigm. The findings are expected to be a reference for educational institutions in improving the attractiveness and quality of study programs.